Diversity And Abundance Of Beetle In The Complex Rice Farming System In Sukorejo Village, Gondanglegi District, Malang Regency - Ayuba, Lang Lang Meilany Noor; Rizali, Akhmad (Journal of Tropical Plant Protection, 2023)
Complex rice systems are a type of farming system that provides shelter for various insects, thereby reducing pests and plant diseases while enhancing farmer's economies. Plants and other components integrated with rice enhance beetle diversity and abundance in complex rice systems. This study aimed to determine the diversity and abundance of beetles in a complex rice system and the factors that can influence them. The study was conducted on a complex rice system farm in Sukorejo Village, Gondanglegi District, Malang Regency. Observations were made five, seven, and nine weeks after planting the rice. Beetles were sampled using pitfall traps and farmcop traps. The results showed differences in the diversity and abundance of beetles between farms with monoculture systems and those with complex rice systems. However, plant age, temperature, and humidity did not correlate with beetle diversity and abundance. This research concludes that complex rice systems are better than monoculture systems.